2011
DOI: 10.1111/j.1445-2197.2011.05668.x
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic value of an initial C‐reactive protein level in acute surgical patients

Abstract: Background: In surgical patients, C-reactive protein (CRP) levels are often measured as a marker of inflammation and infection. However, the diagnostic and prognostic value of a single initial CRP measurement in the acute presentation has not been well established. This study was performed to investigate the usefulness of measuring CRP in such a setting. Methods: CRP levels were measured retrospectively in 473 surgical patients who presented to the Royal Adelaide Hospital emergency department. This was correla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Some studies have reported that there is very little correlation between CRP values and the outcomes of the patient and that CRP alone is not useful in differentiating self-limiting conditions from causes that need surgery. 19 , 20 Conversely, another study demonstrated that increasing levels of CRP predict positive findings on CT with increasing likelihood suggesting that inflammatory markers can be used in prioritizing patients for imaging. 10 …”
Section: Discussionmentioning
confidence: 99%
“…Some studies have reported that there is very little correlation between CRP values and the outcomes of the patient and that CRP alone is not useful in differentiating self-limiting conditions from causes that need surgery. 19 , 20 Conversely, another study demonstrated that increasing levels of CRP predict positive findings on CT with increasing likelihood suggesting that inflammatory markers can be used in prioritizing patients for imaging. 10 …”
Section: Discussionmentioning
confidence: 99%
“…In patients with increasing sepsis biomarkers after surgery a possible iatrogenic driven elevation of these markers due to the surgical trauma per se may lead to misinterpretation of test results and hence of the clinical patient’s condition. Surgical trauma can induce an increase of CRP and IL-6 levels strongly depending on the size of local tissue damage [ 10 ], [ 11 ], [ 12 ]. Previous studies have reported that IL-6, after reaching the peak immediately after surgical intervention decreases rapidly during the first postoperative day [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…I read with interest and with some unhappiness the recent article ‘Diagnostic value of an initial C‐reactive protein level in acute surgical patients’ 1 …”
mentioning
confidence: 99%